PROBLEM LANSIA DAN TINGKAT KEPUASANNYA DALAM MENGIKUTI KONSELING ISLAM - Irman, Irman; Silvianetri, Silvianetri; Zubaidah, Zubaidah (Al-Qalb : Jurnal Psikologi Islam, 2019)
This study aims to reveal the problem of the elderly and determine the level of satisfaction of the elderly in attending counseling. The research method used is the mixed method desigh sequence, a combination of qualitative and quantitative approaches. Qualitative methods are used to explore problems experienced by the elderly and quantitative methods are used to determine the level of satisfaction of the elderly in following Islamic counseling. The research respondents were elderly who were in the Batusangkar Compassionate Nursing Home.The results of the study found that the problem often experienced by the elderly in nursing homes is the inability to manage the mind and feelings to accept the reality.The effects of these problems are; (1) disruption of social interaction, (2) low self-existence, (3) despair, (4) feeling lonely, and (5) feeling guilty. To overcome these problems the elderly get Islamic counseling interventions. The level of satisfaction of the elderly towards Islamic counseling is high, both on aspects of the service process and on aspects of the results of counseling. Islamic counseling can be used to overcome various problems in the elderly.